A Study of Online Customers Repurchase Intention Using the 4Rs of Marketing Framework - Mendoza, Enrico C. (International Review of Management and Marketing, 2021)
With increased e-commerce competition, people are now resorting to online shopping instead of traditional stores to do personal shopping. With the current pandemic, there is more reason why shoppers would not step out of their homes. It’s therefore imperative for companies engaged in e-commerce to find ways on how to influence its customers to do a repeat purchase with an eye towards the long-term goal of cultivating long term relationships with them. The main purpose of this study was to investigate the impact of variables based on the framework of the 4Rs of marketing towards trust and online customers repurchase intentions. Ninety-seven customers of Lazada website participated with data collection done mainly using online questionnaire. Findings indicated that the variables assurance, corporate image, customer satisfaction, perceived usefulness, and perceived value significantly predicted trust and online customer repurchase intentions. Furthermore, the study revealed that trust can be a significant mediator between the abovementioned variables and online customer repurchase intentions. Lastly, this study has provided a useful insight to help managers understand how to maintain a long-term relationship by enhancing its customers repurchase intentions. Considering the intense competition, long term marketing relationship is the only way to go to survive. Keywords: Online Customers Repurchase Intention; 4Rs of Marketing. JEL Classifications: M1; M3 DOI: https://doi.org/10.32479/irmm.11009